2021
DOI: 10.1038/s41467-021-24270-x
|View full text |Cite|
|
Sign up to set email alerts
|

Liquid flow reversibly creates a macroscopic surface charge gradient

Abstract: The charging and dissolution of mineral surfaces in contact with flowing liquids are ubiquitous in nature, as most minerals in water spontaneously acquire charge and dissolve. Mineral dissolution has been studied extensively under equilibrium conditions, even though non-equilibrium phenomena are pervasive and substantially affect the mineral-water interface. Here we demonstrate using interface-specific spectroscopy that liquid flow along a calcium fluoride surface creates a reversible spatial charge gradient, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 44 publications
5
50
0
8
Order By: Relevance
“…It is found that the second-force equilibrium equation [33] has been proved by the experiments. A few inferences derived from the second-force equilibrium equation are consistent with the experimental results [34,35]. After finding the verification experiments of the second-force equilibrium equation, we have more confidence in the second-precession equilibrium equation.…”
Section: Introductionsupporting
confidence: 79%
“…It is found that the second-force equilibrium equation [33] has been proved by the experiments. A few inferences derived from the second-force equilibrium equation are consistent with the experimental results [34,35]. After finding the verification experiments of the second-force equilibrium equation, we have more confidence in the second-precession equilibrium equation.…”
Section: Introductionsupporting
confidence: 79%
“…Interfacial charge dynamics is ultimately determined by physicochemical processes, such as dissociation of charged functional groups or specific adsorption of ions (12)(13)(14)(15), which occur in the few layers of molecules at the interface between the solid surface and the solvent. While new insights have been obtained thanks to electrokinetic measurements (16,17), second harmonic generation (18)(19)(20), dynamic atomic force microscopy (21), or time-resolved fluorescence (22,23), our fundamental understanding of the dynamics of these interfacial processes remains poor (24,25) because of the difficulties in obtaining surface-specific information at both high spatial and temporal resolution. In this context, we could recently resolve the diffusive dynamics of individual excess proton charge at the interface between defected hexagonal boron nitride (hBN) and aqueous solutions (26).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in atomic force microscopy experiments on silica with tip speeds as fast as 0.5 μm=s, charge regulation due to the EDL overlap between the surface and tip is so fast that no hysteresis is observed in force-distance curves [5]. This suggests that surface chemistry adapts within milliseconds-a value consistent with flow experiments on mineral surfaces probing the electronic response induced by composition changes [6][7][8]. Dissolution experiments also provide lower bounds for protolysis rates.…”
mentioning
confidence: 64%